Control interno y su relación con la calidad de los servicios que brinda la Unidad De Quemados Del Hospital Luis Vernaza en la ciudad de Guayaquil, año 2014 - Pilay Tubay, Lorenzo Valentín (2015)
This research was performed at the Luis Vernaza Hospital in the city of Guayaquil, it is part of the conglomerate of public institutions that are subject to ongoing assessments to measure customer satisfaction, so it is necessary to evaluate internal control and its relationship with the quality of the services provided by the burn unit of the hospital Luis Vernaza in the city of Guayaquil, 2014. The rates applied field research were descriptive and literature; methods of historical research logical, analytic and synthetic observation; control environment, risk assessment, control activities, information and communication, supervision and monitoring: research design trends of the five components was performed. The investigation concluded that the Luis Vernaza hospital has 56 medical residents, 73 licensed nurses, 178 nursing assistants, and 139 physicians in 35 specialties, resulting in a 70% degree of satisfaction of patients. In the Burns Unit of Hospital found that the hospital has trained professionals for the respective patient care, which gave their opinion about the quality of services obtained indicators fall and impact are considered 100% relevant. The analysis by the Internal Control COSO method I which consists of five components that allowed timely assess the area resulted in the percentage of risks facing the burn unit of the Hospital Luis Vernaza which are: Level of Confidence high of 80.95% and low risk level of 19.05%, which places it in a reasonable range indicating that effective controls for the proper functioning of the organization applies, and is reflected in the satisfaction of the community.